2020
DOI: 10.3389/fspor.2020.00089
|View full text |Cite
|
Sign up to set email alerts
|

Ski Skating Race Technique—Effect of Long Distance Cross-Country Ski Racing on Choice of Skating Technique in Moderate Uphill Terrain

Abstract: The aim of this study was to investigate the effect of prolonged ski racing using skating style on technique choice in a transition section among female and male high-level skiers. Fifty three national-to-elite level skiers (20 females: 26.7 ± 4.8 years, 167.0 ± 6.5 m, 61.0 ± 5.1 kg, and 75.5 ± 68.8 FIS points; 33 males: 25.2 ± 3.5 years, 179.0 ± 5.2 cm, 73.1 ± 5.7 kg, and 73.7 ± 63.2 FIS points) were video recorded along a flat-to-uphill transition section of a course during the 30-km (females) and 50-km (mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…These findings might reflect different micro-pacing strategies adopted between sexes, as well as different relative strengths in women and men. Sex differences in the fastest vs. slowest skier might be explained by variations in skiing speed during transitional periods between flat and uphill sections (Ardigò et al, 2020 ). Although the FIS points were similar between sexes in the present study, there was a greater variation in the male athletes, which might explain why larger time differences were observed in this cohort.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings might reflect different micro-pacing strategies adopted between sexes, as well as different relative strengths in women and men. Sex differences in the fastest vs. slowest skier might be explained by variations in skiing speed during transitional periods between flat and uphill sections (Ardigò et al, 2020 ). Although the FIS points were similar between sexes in the present study, there was a greater variation in the male athletes, which might explain why larger time differences were observed in this cohort.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that pacing strategies in XC skiing might vary depending on sex (Losnegard et al, 2016 ; Andersson et al, 2019 ; Ardigò et al, 2020 ), skiing technique (Stöggl et al, 2018 ; Ardigò et al, 2020 ) and competition distance (Losnegard et al, 2016 ). For instance, men tend to ski with a greater relative power output during uphill sections compared to women (Andersson et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation